2019
DOI: 10.1186/s13073-019-0659-1
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Markov models lead to higher resolution maps of mutation signature activity in cancer

Abstract: Knowing the activity of the mutational processes shaping a cancer genome may provide insight into tumorigenesis and personalized therapy. It is thus important to characterize the signatures of active mutational processes in patients from their patterns of single base substitutions. However, mutational processes do not act uniformly on the genome, leading to statistical dependencies among neighboring mutations. To account for such dependencies, we develop the first sequence-dependent model, SigMa, for mutation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…While the expression correlation patterns of all other APOBEC signatures are consistent with such understanding, Signature 2D exposure level has slightly negative correlation with immune response (2A, aC6). This is consistent with our previous observation that there is no positive correlation between Signature 2D and APOBEC expression [9]. In addition, Signature 2 exposure level is either not correlated (2D) or has a weak correlation (2C) with the cluster enriched with translesion synthesis (2, aC7 and mC4) whereas both Signature 13C and 13D show strong positive correlation.…”
Section: Expression Analysis To Identify Biological Processes Associasupporting
confidence: 92%
See 4 more Smart Citations
“…While the expression correlation patterns of all other APOBEC signatures are consistent with such understanding, Signature 2D exposure level has slightly negative correlation with immune response (2A, aC6). This is consistent with our previous observation that there is no positive correlation between Signature 2D and APOBEC expression [9]. In addition, Signature 2 exposure level is either not correlated (2D) or has a weak correlation (2C) with the cluster enriched with translesion synthesis (2, aC7 and mC4) whereas both Signature 13C and 13D show strong positive correlation.…”
Section: Expression Analysis To Identify Biological Processes Associasupporting
confidence: 92%
“…In this study we consider mutational signatures in cancer patients and attempt to identify genes and pathways whose expression and/or genetic alterations are potentially causative of differences in mutational signature strength. Since recent studies revealed that mutations occurring in close proximity to each other, referred to here as cloud mutations, have distinct properties from dispersed mutations [35,9], we additionally subdivided all mutations (and subsequently their attributed signatures) into two groups -close-by Cloud mutations and Dispersed mutations. We used only sufficiently abundant mutational signatures for cloud or dispersed mutations in the cohort of 560 breast cancer genomes [23], as inferred by a recently developed HMM based approach -SIGMA [9].…”
Section: Analysis Overviewmentioning
confidence: 99%
See 3 more Smart Citations